The differing pathophysiologies that underlie COVID‐19‐associated perniosis and thrombotic retiform purpura: a case series - Magro, C.M. (Br J Dermatol, 2021)
BACKGROUND: There are two distinctive acral manifestations of COVID‐19 embodying disparate clinical phenotypes. One is perniosis occurring in mildly symptomatic patients, typically children and young adults; the second is the thrombotic retiform purpura of critically ill adults with COVID‐19. OBJECTIVES: To compare the clinical and pathological profiles of these two different cutaneous manifestations of COVID‐19. METHODS: We compared the light microscopic, phenotypic, cytokine and SARS‐CoV‐2 protein and RNA profiles of COVID‐19‐associated perniosis with that of thrombotic retiform purpura in critical patients with COVID‐19. RESULTS: Biopsies of COVID‐19‐associated perniosis exhibited vasocentric and eccrinotropic T‐cell‐ and monocyte‐derived CD11c(+), CD14(+) and CD123(+) dendritic cell infiltrates. Both COVID‐associated and idiopathic perniosis showed striking expression of the type I interferon‐inducible myxovirus resistance protein A (MXA), an established marker for type I interferon signalling in tissue. SARS‐CoV‐2 RNA, interleukin‐6 and caspase 3 were minimally expressed and confined to mononuclear inflammatory cells. The biopsies from livedo/retiform purpura showed pauci‐inflammatory vascular thrombosis without any MXA decoration. Blood vessels exhibited extensive complement deposition with endothelial cell localization of SARS‐CoV‐2 protein, interleukin‐6 and caspase 3; SARS‐CoV‐2 RNA was not seen. CONCLUSIONS: COVID‐19‐associated perniosis represents a virally triggered exaggerated immune reaction with significant type I interferon signaling. This is important to SARS‐CoV‐2 eradication and has implications in regards to a more generalized highly inflammatory response. We hypothesize that in the thrombotic retiform purpura of critically ill patients with COVID‐19, the vascular thrombosis in the skin and other organ systems is associated with a minimal interferon response. This allows excessive viral replication with release of viral proteins that localize to extrapulmonary endothelium and trigger extensive complement activation.